2013
DOI: 10.1021/jp406491q
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Vanadium States and Oxygen Vacancies in the Structural and Optical Properties of TiO2:V Thin Films

Abstract: In this work, we present the customized modifications in the morphology and optical properties of vanadium (V) doped TiO 2 thin films sputter deposited on glass substrates at a growth rate of ∼0.6 Å/s at 500 °C. The sputtering targets of pure and V doped TiO 2 with three concentrations of V (1.0, 1.5, and 2.0 atomic percentage (at. %)) were prepared from powders. XRD patterns confirmed the grown TiO 2 films were anatase. In the doped TiO 2 films, the crystallite size reduced by almost half when the V concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…The oxide particles with a high density of oxygen vacancies can give rise to in-gap states or surface states that yield a continuum of below bandgap absorbances. 24,25 Such defects may be the origin of the observed photoluminescence in the wavelength range from 450 nm to 575 nm. There is a decrease in photoluminescence intensity in proceeding from bare TiO 2 to the nanocomposite sample expect to a broad band around 593 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The oxide particles with a high density of oxygen vacancies can give rise to in-gap states or surface states that yield a continuum of below bandgap absorbances. 24,25 Such defects may be the origin of the observed photoluminescence in the wavelength range from 450 nm to 575 nm. There is a decrease in photoluminescence intensity in proceeding from bare TiO 2 to the nanocomposite sample expect to a broad band around 593 nm.…”
Section: Resultsmentioning
confidence: 99%
“…54,55 The green curve at 520 eV corresponds to the O 1s satellite. 56 The results of curve fitting in Figure 5c suggest that all samples contain V 5+ species. Moreover, one can clearly observe a shoulder in the 5% V-Ti-700, 10%V-Ti-700, and 10%V-Ti-800 samples, which can be assigned to the V 4+ species.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…However, its efficiency is limited by its wide bandgap (*3.0 eV) because it could be activated only under the UV irradiation, and the photoinduced electron-hole pairs can recombine easily as well. To reduce the bandgap and improve the efficiency, considerable experimental and theoretical efforts have been carried out, such as doping (including metal, non-metal, and codoping) [2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], defect engineering (including oxygen vacancy and Ti interstitial) [23][24][25][26][27][28][29][30][31], and surface coating (such as metal and semiconductor nanoparticles) [32][33][34][35][36]. Recently, Etacheri et al [37] reported that the visible-light photocatalytic activity of undoped TiO 2 was achieved by increasing the amount of oxygen in TiO 2 .…”
Section: Introductionmentioning
confidence: 99%